Tempe Gembus Intervention Decreased Total Cholesterol And Triglyceride In Obese Women - Isnawati, Muflihah; Wijaningsih, Wiwik; Tursilowati, Susi (Poltekkes Kemenkes Semarang, 2024)
Obesity increases cardiovascular risk through dyslipidaemia. High fibre diet reduces risk factors of dyslipidaemia by up to 50%. Tempe gembus is a solid fermented food made from tofu waste product with rhyzopus-oligosporus, that contained high fibre. The purpose of this study is to determine the effect of the administration processed tempe gembus on lipid profiles in obese women. This study was pre-post randomized control group design. Forty-four pre-menopausal women with obesity, dyslipidaemia took part in this study, divided into 2 groups, includes the intervention group and the control group. The Intervention group received 150 gram of processed tempe gembus for 28 days. Statistical analysis independent sample test or Mann Witney were used to analyse differences pre and post-lipid profile between intervention and control group.Â Â Consumption of 150 g/day of processed tempe gembus for 28 days reduced total cholesterol levels by 13.4 mg/dl (p = 0.012), HDL cholesterol by 2.8 mg/dl (p = 0.082), LDL cholesterol by 17.6 mg/dl (p = 0.52) and triglyceride levels of 5.3 mg/dl (p = 0.05), respectively. There was significant effect of processed tempe gembus consumption to reduce total cholesterol, and triglycerides. Unfortunately, there were no effect on LDL and HDL cholesterol.